From one place to another: setting out the temporal warp place by inserting fragments. The Monastery of Santa Maria de las Cuevas in Seville - García de Casasola, Marta; Moreno, José Ramón (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
The definition of the heritage object as a starting point to recognise a past place implies the assumption of a temporary aporia. We work with objects which come from a past, brought to a problematic present by the heritage exercise; we just keep pieces or ruins from them, even just emptiness. Intervening in heritage means, therefore, to work also with absences, through recognition of traces now understood as overlapping layers identified to build the object we face. Architecture opposite Heritage has got the responsability of knoweledge transfer through an disclosure exercise. To illustrate this task, we turn to a fountain placed at a threshold of the Monastery of Santa Maria de las Cuevas in Seville, or to a threshold where the fountain is placed. A maze of questions that constitutes itself a planning exercise.